2014
DOI: 10.1039/c4ra08515a
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal nanohybrid cerasomes for controlled insulin release

Abstract: This study reported a facile fabrication of a reproducible and injectable cerasomal insulin formulation by encapsulating insulin into cerasomes via one-step construction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
(46 reference statements)
0
13
0
Order By: Relevance
“…As an emerging platform, partially silica-coated organic-inorganic nanohybrid (cerasomes) exhibit integrated properties of traditional lipid-based NPs and inorganic silica NPs. Cerasomes are biomimetic colloidal NPs with an additional layer of the polyorganosilxane network which imparts cerasomes with higher stability than conventional liposomes (Jin et al, 2014 ). Nano-sized cerasomal NPs have various advantages, including biocompatibility, prolonged blood circulation, higher tumor accumulation by enhanced permeability and retention (EPR) effect, and decreased reticuloendothelial system (RES) clearance (Jin et al, 2014 ).…”
Section: Nanocarriers: Recent Advances and Challengesmentioning
confidence: 99%
See 3 more Smart Citations
“…As an emerging platform, partially silica-coated organic-inorganic nanohybrid (cerasomes) exhibit integrated properties of traditional lipid-based NPs and inorganic silica NPs. Cerasomes are biomimetic colloidal NPs with an additional layer of the polyorganosilxane network which imparts cerasomes with higher stability than conventional liposomes (Jin et al, 2014 ). Nano-sized cerasomal NPs have various advantages, including biocompatibility, prolonged blood circulation, higher tumor accumulation by enhanced permeability and retention (EPR) effect, and decreased reticuloendothelial system (RES) clearance (Jin et al, 2014 ).…”
Section: Nanocarriers: Recent Advances and Challengesmentioning
confidence: 99%
“…Cerasomes are biomimetic colloidal NPs with an additional layer of the polyorganosilxane network which imparts cerasomes with higher stability than conventional liposomes (Jin et al, 2014 ). Nano-sized cerasomal NPs have various advantages, including biocompatibility, prolonged blood circulation, higher tumor accumulation by enhanced permeability and retention (EPR) effect, and decreased reticuloendothelial system (RES) clearance (Jin et al, 2014 ). Thus, cerasomal NPs are capable of overcoming pharmacological limitations with substantial advantages over conventional nanocarriers (Yue and Dai, 2014 ).…”
Section: Nanocarriers: Recent Advances and Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, composite cerasomes could optimize the release profile of HCPT by the alteration in vesicle compositions, leading to a significantly improved pharmacokinetic profile in vivo. Similarly, Jin et al [43] reported the fabrication of composite cerasomes for controlled insulin release by altering vesicle composition through incorporating the phospholipid of DPPC into cerasomes. More importantly, the insulin-loaded composite cerasomes showed a significant and prolonged hypoglycaemic effect compared with liposomes and free insulin.…”
Section: Applications Of Cerasomes As Drug Nanocarriersmentioning
confidence: 99%